Air–Fuel Ratio Evaluation in Open-Loop ECU Mapping for a KZR Engine: A Trade-Off Analysis of Power, Torque, and Fuel-Efficiency Potential - Muhammad Ilham Ramadhan; Tatang Permana (Universitas Negeri Padang, 2026)
An open-loop ECU operates without oxygen-sensor feedback, making Air–Fuel Ratio (AFR) control dependent on the preset fuel map. This study evaluated how three AFR settings in open-loop ECU mapping relate to the performance characteristics of a Honda KZR engine. A dynamometer-based experiment was conducted on a Honda Vario 125 KZR engine using Pertalite RON 90 and AFR targets of 11.7, 13.1, and 14.1. The evaluated parameters were engine power, torque response, and fuel-efficiency potential inferred from AFR characteristics. The results showed that AFR 13.1 produced the highest reported power output of 11.0 HP, whereas AFR 14.1 indicated a more favourable fuel-efficiency potential. AFR 11.7 represented an over-rich setting with the least favourable efficiency tendency. These findings indicate a trade-off between performance-oriented and economy-oriented AFR settings in open-loop ECU mapping.